Urgensi Komunikasi Efektif dalam Organisasi - Moh. Yamin Rumra (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Effective communication plays an important role in determining the success of an organization, whether in the government, business, or social organization sectors. Communication is not just a process of conveying information, but also how messages are understood and responded to appropriately by each individual involved. This article aims to discuss the urgency of effective communication in organizations, its supporting elements, obstacles that are often faced, and strategies for creating effective communication. The writing method uses a literature study with a qualitative descriptive approach through various relevant literature sources. The results of the discussion show that effective communication can increase job satisfaction, productivity, and build healthy interpersonal relationships. Supporting factors such as openness, empathy, supportive attitudes, positive attitudes, and equality are important indicators in creating effective communication. On the other hand, obstacles such as differences in perception, emotions, information overload, and cultural backgrounds must be recognized and overcome. By consistently applying the principles of effective communication, organizations can minimize conflict, build a harmonious work environment, and improve performance sustainably.